Education Decentralization and Accountability Relationships in Latin America - di Gropello, Emanuela (World Bank, Washington, D.C., 2013)
The author analyzes decentralization reforms in the education sector in Latin America (their status, impact, and ongoing challenges) by making use of the accountability framework developed by the World Development Report 2004: Making Services Work for Poor People. She starts by identifying three main groups of models according to the subnational actors involved, the pattern adopted in the distribution of functions across subnational actors, and the accountability system central to the model. She then reviews the impact of these models according to the available empirical evidence, and explores determinants of this impact, extracting lessons useful to the design of future reforms. The author concludes that the single most important factor in ensuring the success or failure of a reform is the way the accountability relationships are set to work within each of the models and provides some lessons on how to get these relationships to work effectively. She also provides three main general lessons for selecting "successful" models: (1) avoid complicated models; (2) increase school autonomy and the scope for "client power," maintaining a clear role for the other accountability relationships; and (3) place more emphasis on the "management" accountability relationship and the sustainability of the models.